THE REASONS FOR THE CRISIS AND THE END OF THE KHIVA KHANATE - Sharifov Ehronbek Erkin oglu (Scholar Express Journal, 2025)
This article examines the complex political history of the Khiva Khanate, from its formation in the 16th century to its decline and eventual end. It details the constant internal strife, power struggles among competing factions of Uzbek and Turkmen tribes, and the frequent changes in leadership that plagued the khanate. The text highlights how these internal conflicts, coupled with external pressures from neighboring powers like the Bukhara Khanate and the Russian Empire, contributed to the state's political instability. Key events discussed include the relocation of the capital to Khiva, the reigns of influential figures such as Abulgazi Khan and Shergozi Khan, and the devastating invasion by Nadir Shah of Iran. The article argues that a combination of internal fragmentation, dynastic rivalries, and growing external interference ultimately led to the crisis and the collapse of the Khiva Khanate.
Keywords: Khiva Khanate; Political instability; Dynastic struggle